The first subterranean ant species of the genus Meranoplus F. Smith, 1853 (Hymenoptera: Formicidae) from Vietnam - V.A. Zryanin (Кавказский энтомологический бюллетень, 2015)
A subterranean ant species of the subfamily Myrmicinae, Meranoplus dlusskyi sp. n., is described based on workers recovered from a soil-core sample taken in a primary tropical monsoon forest of Southern Vietnam. Membership of the species in the genus Meranoplus F. Smith, 1853 is confirmed by all key characters including 9-merous antennae with 3-merous club and the structure of the sting apparatus, but unique characteristics, reflecting evolutionary trends toward a subterranean existence, are found. These include an almost complete reduction of eyes, an obsolete promesonotal shield, shortened appendages, depigmentation of cuticle and its superficial sculpture. Significant difference from all described species of the genus is the palp formula 3.3  vs.  5.3. No species with a subterranean lifestyle have hitherto been known in this genus. The presence of 5  mandibular teeth, absence of the clypeal armament, form of the propodeum, which constitutes part of the dorsal alitrunk (rather ancestral conditions) all suggest an early separation of the M. dlusskyi sp.  n. lineage. The concept of ousted relicts is used for explaining the possible origin of this lineage and recent distribution of Meranoplus as a whole